Estrutura e dinâmica dos agentes da cadeia produtiva do café conilon no estado do Espírito Santo - Lubiana, Cleidice (2003)
The objective of work consist in characterize the structure and identify the dynamics of development of agents from the productive chain of conilon coffee in the state of Espírito Santo. The methodology that was used based in the qualitative research, by means of exploitable study and descriptive witer, utilization from logbook by interviews. Divided in five groups: process, technologies of production, information, interrelations and professionalization / mechanisms of coordination. Verified anself that inside the variables that influency the development of the agent inside that your segment and in relation the other segments of chain. Went principally the variable information. Knowledge and chain and interrelations. All that great the grade of knowledge and development in this variable, the better is your position. In isolation segments observed anself on heterogeneity of agents, marked for differences existents in portage and professionalism in activity. Every agent, in your segment, actuate according whit necessity that your activity, no existing the preoccupation of the verified the impact that your actions in the chain as all. Agents that present great information that dispose more professionalization and maintain the great number of interrelations in comparison with besides components of the chain at form indirect, were that conduct the directions from the productive chain of coffee leaving to besides, the part of follower.